2003
DOI: 10.1074/jbc.m212235200
|View full text |Cite
|
Sign up to set email alerts
|

Parkin Facilitates the Elimination of Expanded Polyglutamine Proteins and Leads to Preservation of Proteasome Function

Abstract: Parkin, the most commonly mutated gene known to result in familial Parkinson's disease (PD), 1 encodes an E3 ubiquitin ligase (1). Several substrates for parkin have been identified including CDCrel-1, an o-glycosylated form of ␣-synuclein ␣Sp22, Pael-R (2), and synphilin-1 (3-5). These parkin substrates have little sequence or functional similarities; however, Pael-R and ␣-synuclein have a propensity to misfold and aggregate (2, 4). This common property of known parkin substrates suggests that parkin may play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
177
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(183 citation statements)
references
References 83 publications
5
177
0
Order By: Relevance
“…A total of 95.9% of the proton, nitrogen, and carbon chemical shifts were assigned and used to calculate the three-dimensional structure of IBR . This resulted in a total of 1,263 distance restraints derived from 13 C-edited, 15 N-edited, and 1 H-1 H NOESY spectra (SI Table 1). Initial structures were calculated in the absence of Zn 2ϩ ion restraints to determine the overall fold of the domain.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 95.9% of the proton, nitrogen, and carbon chemical shifts were assigned and used to calculate the three-dimensional structure of IBR . This resulted in a total of 1,263 distance restraints derived from 13 C-edited, 15 N-edited, and 1 H-1 H NOESY spectra (SI Table 1). Initial structures were calculated in the absence of Zn 2ϩ ion restraints to determine the overall fold of the domain.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly to Ubp6, parkin requires its Ubl domain to interact with the 26 S proteasomes, at least in vitro (31). However, the exact protein(s) within the proteasome involved in parkin binding, as well as the physiological relevance of this interaction, have not been completely elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the Ubl functions as a key interaction module allowing parkin to interact with proteins containing ubiquitin-binding domains, such as Eps15, Ataxin-3, and endophilin-A (8,10,30). Interestingly, Tsai et al (31) showed that the Ubl domain of parkin is necessary for its direct interaction with purified 26 S proteasomes in vitro. Additionally, two independent groups found that parkin could interact with the 26 S proteasome by binding the 19 S proteasome subunit Rpn10/S5a (32) or the 20 S subunit ␣4/PSMA7 (33).…”
mentioning
confidence: 99%
“…The nature of such signals is unknown, but it has been proposed that exposed hydrophobic domains normally buried in the interior of the protein or in the protein-protein interaction interfaces may serve as recognition signals for the ubiquitination machinery (42,43,51). Interestingly recent evidence indicates that the PD-associated E3 ubiquitin-protein ligase parkin may facilitate the ubiquitination and degradation of misfolded proteins such as Pael-R and the polyglutamine-containing proteins in conjunction with the molecular chaperone Hsp70 and its binding partner carboxyl terminus of Hsp70-interacting protein (52)(53)(54). It would be worthwhile to determine whether parkin has a role in facilitating the ubiquitination of the L166P mutant DJ-1 protein.…”
Section: Discussionmentioning
confidence: 99%